Vote! : women's fight for access to the ballot box - Frazer, Coral Celeste (Twenty-First Century Books, 2020)
Commemorates the one-hundred-year anniversary of the Nineteenth Amendment by documenting the history and struggle for women's right to vote. Highlights key figures in the movement, includes information on how antislavery and women's suffrage leaders became allies, and details the incremental steps that led up to the passing of the Amendment. Expands to cover African Americans' fight against Jim Crow laws of the South designed to prevent them from voting and other women's rights causes in the twentieth century. Calls out current attacks against voter freedoms including voter purging, gerrymandering, and voter ID laws. Photographs, sidebars, and a glossary are interspersed throughout the book.